Neonatal Lethality, Dwarfism, and Abnormal Brain Development in Dmbx1 Mutant Mice - Ohtoshi, Akihira (American Society for Microbiology, 2004)
Dmbx1 encodes a paired-like homeodomain protein that is expressed in developing neural tissues during mouse embryogenesis. To elucidate the in vivo role of Dmbx1, we generated two Dmbx1 mutant alleles. Dmbx1(−) lacks the homeobox and Dmbx1(z) is an insertion of a lacZ reporter gene. Dmbx1(z) appears to be a faithful reporter of Dmbx1 expression during embryogenesis and after birth. Dmbx1-lacZ expression was detected in the superior colliculus, cerebellar nuclei, and subpopulations of the medulla oblongata and spinal cord. Some Dmbx1 homozygous mutant mice died during the neonatal period, while others survived to adulthood; however, their growth was impaired. Both heterozygous and homozygous mutant offspring from Dmbx1 homozygous mutant females exhibited a low survival rate and poor growth. However, even wild-type pups fostered onto Dmbx1 homozygous mutant females grew poorly, suggesting a Dmbx1-dependent nursing defect. Dmbx1 mutant mice had an aberrant Dmbx1-lacZ expression pattern in the nervous system, indicating that they had abnormal brain development. These results demonstrate that Dmbx1 is required for postnatal survival, growth, and brain development.